Ring current instabilities excited by the energetic oxygen ions - Kakad, Amar; Singh, S.V.; Lakhina, G.S. (My University, 2007)
The ring current instabilities driven by the energetic oxygen ions are investigated during the magnetic storm. The electrons and protons are considered to have Maxwellian distributions, while energetic oxygen ions are having loss-cone distribution. Dispersion relation for the quasielectrostatic modes with frequencies ω>ωcp(proton cyclotron frequency) and propagating obliquely to the magnetic field is obtained. Dispersion relation is studied numerically for the storm time ring current parameters and it is found that these instabilities are most prominent during intense storms when the oxygen ions become the dominant constituents of the ring current plasma. For some typical storm-time ring current parameters, these modes can produce quasielectrostatic noise in the range of 17–220Hz, thus providing a possible explanation of the electrostatic noise observed at the inner boundary of the ring current during magnetic storms. Further, these modes can attain saturation electric fields of the order of 100–500μV∕m, and therefore, are expected to scatter O+ ions into the loss-cone giving rise to their precipitation into the atmosphere, thus contributing to the ring current decay.
Keywords: Magnetic storm; Storm time ring current; Ring current; Energetic oxygen ions; Ring current plasma.